Clinical utility of various liquid biopsy samples for the early detection of ovarian cancer: a comprehensive review - Feng, Yueqi; Yang, Wanjun; Zhu, Jingyu; Wang, Shirui; Wu, Ningjuan; Zhao, Hanzhi; Yang, Xiaofeng (Frontiers in Oncology, 2025)
Ovarian cancer (OC) is a highly lethal gynecologic malignancy because of the absence of specific early symptoms and reliable biomarkers, most OC patients are often diagnosed at advanced stages, resulting in poor prognosis. Traditional tissue biopsy and serological biomarkers like CA125 have limited clinical application. Therefore, there is an urgent demand for effective diagnostic and screening tools in clinical practice. Liquid biopsy is a non-invasive method for early cancer detection by analyzing tumor-associated components shed into different body fluids, for example, circulating tumor DNA (ctDNA), circulating tumor cells (CTCs), cell-free RNA, proteins, and metabolites. Increasing evidence has demonstrated that liquid biopsy is promising for detecting cancer at an early stage. In this review, we outline the results for the utility of each liquid biopsy fluid, including serum/plasma, urine, cervical/vaginal sample, uterine lavage, and summarize the advantages and current constraints associated with their application in clinical settings. Future directions and challenges are also highlighted, along with areas where more research is warranted.